PROBIOTICS AND BACTERIAL IMMUNOMODULATORS FOR PREVENTION OF RESPIRATORY INFECTIONS - N. V. Khoroshilova (Вопросы современной педиатрии)
Frequent respiratory infections are the risk factor of development of chronic inflammatory diseases of a respiratory tract, bronchial asthma, and owing to arising disorders in the immunity system at the level of mucous membranes they can lead to an inflammation of a mucous membrane of a digestive and urogenital tract. Traditionally the prevention of acute respiratory infections includes sanitation of the centers of infections, and also elimination of dysbiosis and immune imbalance with the application of probiotics and bacterial immunomodulators. Therewith the probiotic means are necessary not only for restoration of normal microflora on mucous membranes (first of all, in a gastrointestinal tract), but also for optimization of immunocorrective therapy, especially when oral immunomodulators are used.